The Relationship between Self-Care Agency and the Level of Disability to Patient with Leprosy at Daha Husada Hospital, Kediri - Widyowati, Agustin; Hapsari, Ika Ratna; Nuridayanti, Anik (Indonesian Journal of Medicine, 2022)
Background: Leprosy has a tendency to have physical impacts with disability on sufferers so that it affects community stigma, social isolation, welfare to quality of life. One of the efforts to prevent disability with good self-care. The objective was to determine the relationship between self-care agency and the level of disability to patients with leprosy at Daha Husada Hospital Kediri.Subjects and Method: A cross sectional study was conducted in Daha Husada Hospital, Kediri, East Java, in March, 2021. A sample of 115 patients was selected by purposive sampling. The dependent variable was the level of disability. The independent variable was self-care agency. Data were collected using questionnaires and observation sheets with ordinal scale, then analyzed using statistical test of Spearman's Rho.Results: Less ability of leprosy patients in self care agency, the greater the level of disability (r= 0.62; p<0.001).Conclusion: Less ability of leprosy patients in self-care agency, the greater level of disability. Patient are needed to improve the awareness in self-care activities and follow counseling in health services.Keywords: self care agency, the level of disability, patient with leprosy.Correspondence: Agustin Widyowati. STRADA Indonesian Institute of Health Sciences Kediri. Jl. Manila No.37, Tosaren, Kec. Pesantren, Kota Kediri, East Java 64123. Email: agustwidy@gmail.com. Mobile: +62857-3539-9728.Indonesian Journal of Medicine (2022), 07(03): 344-349https://doi.org/10.26911/theijmed.2022.07.03.11